Associations of Inflammation with Frailty in Patients with Breast Cancer Aged 50 and Over Receiving Chemotherapy - Gilmore, Nikesha (J Geriatr Oncol, 2019)
PURPOSE: Chronic inflammation is a significant physiologic feature of frailty; however, its role and clinical utility in cancer-related frailty remains unknown. We sought to determine if pre-chemotherapy inflammation is predictive of frailty after chemotherapy in patients with breast cancer. METHODS: Female patients (N=144; age ≥50) with stage I-III breast cancer scheduled to receive chemotherapy and age-matched non-cancer controls (N=142) were included in this secondary analysis and assessed pre- and post-chemotherapy. Controls were assessed at equivalent time-points. Frailty was assessed using a modified Fried’s score (0-4) using self-reported measures of weakness, exhaustion, walking speed, and physical activity. Serum levels of interleukin (IL) 6, and soluble tumor necrosis factor-alpha (sTNFR) I and II were measured. Associations between pre-chemotherapy cytokine and receptors level (median as cutoff) and post-chemotherapy frailty were evaluated using T-tests. RESULTS: Pre-chemotherapy, patients with breast cancer were more frail than non-cancer controls (mean score: 1.17 vs 0.65; p<0.01). Patients also became more frail post-chemotherapy (mean score: 1.17 vs 2.08; p<0.01). Patients with pre-chemotherapy serum levels of IL-6, sTNFRI, and sTNFRII above the median were more frail after chemotherapy than those with levels below the median [IL-6 (2.31 vs. 1.86; p=0.03), sTNFRI (2.30 vs. 1.88; p=0.04), and sTNFRII (2.30 vs. 1.88; p=0.04)]. No differences were observed in non-cancer controls within the same timeframe. CONCLUSIONS: Both cancer and chemotherapy were associated with frailty. Higher pre-chemotherapy inflammatory cytokine levels were associated with post-chemotherapy frailty. This supports the utility of inflammatory cytokines to identify patients who develop worsening of frailty characteristics with chemotherapy.